Circulating C-Type Natriuretic Peptide and Its Relationship to Cardiovascular Disease in the General Population. Issue 6 (June 2015) - Sangaralingham, S. Jeson; McKie, Paul M.; Ichiki, Tomoko; Scott, Christopher G.; Heublein, Denise M.; Chen, Horng H.; Bailey, Kent R.; Redfield, Margaret M.; Rodeheffer, Richard J.; Burnett, John C.
<x xml:space="preserve">Abstract</x> C-type natriuretic peptide (CNP) is an endothelium-derived peptide that is released as a protective mechanism in response cardiovascular injury or disease. However, no studies have investigated circulating CNP, identifying clinical factors that may influence CNP and its relationship to cardiovascular disease in the general population. We studied 1841 randomly selected subjects from Olmsted County, MN (mean age, 63±11 years; 48% men). Plasma CNP was measured by a well-established radioimmunoassay and echocardiography, clinical characterization, and detailed medical record review were performed. We report that CNP circulates at various concentrations (median, 13 pg/mL), was unaffected by sex, was weakly associated by age, and that highest quartile of CNP identified a high-risk phenotype. Subjects with CNP in the highest quartile were associated with increased risk of myocardial infarction (multivariable-adjusted hazard ratio, 1.51; 95% confidence interval, 1.09–2.09; P=0.01) but not heart failure, cerebrovascular accidents, or death during a follow-up of 12 years. Addition of the highest quartile of CNP to clinical variables led to a modest increase in the integrated discrimination improvement for risk of myocardial infarction. In a large community-based cohort, elevated circulating CNP identified a high-risk phenotype that included cardiovascular comorbidities and left ventricular dysfunction, and provided evidence that highest concentrations of CNP potentially has prognostic value in predicting future risk of myocardial infarction. Together, these data from the general population highlight the potential value of CNP and support the need for additional studies to evaluate whether mechanisms regulating CNP could improve outcomes.